Allelic variations in superoxide dismutase-1 (SOD1) gene are associated with increased risk of diabetic nephropathy in type 1 diabetic subjects - Mohammedi, Kamel; Maimaitiming, Suliya; Emery, Nathalie; Bellili-Muñoz, Naima; Roussel, Ronan; Fumeron, Frédéric; Hadjadj, Samy; Marre, Michel; Velho, Gilberto (Molecular genetics and metabolism, 2011)
Oxidative stress is involved in the pathophysiology of diabetic nephropathy. The superoxide dismutase (SOD) enzymes play a major role in detoxification of reactive oxygen species and have a protective effect against diabetic nephropathy. We investigated associations of allelic variations in SOD1 gene with nephropathy in patients with type 1 diabetes. Seven SNPs in SOD1 region were analyzed in 1285 type 1 European Caucasian diabetic patients from the SURGENE prospective study (n=340; ten year follow-up), and the Genesis France-Belgium (n=501) and GENEDIAB (n=444) cross-sectional studies. Cox proportional hazards and logistic regression analyses were used to estimate hazard ratios or odds ratios for incidence and prevalence of diabetic nephropathy. In the SURGENE study, the T-allele of rs1041740 was associated with the prevalence of incipient (OR 5.75, 95% CI 1.78–19.39, p=0.004) and established/advanced nephropathy at baseline (OR 8.95, 95% CI 1.51–58.42, p=0.02), and with the incidence of incipient nephropathy during follow-up (HR 1.46, 95% C.I. 1.13–1.90, p=0.004). The variant was also associated with decreased estimated glomerular filtration rate (eGFR) throughout the study. In cross-sectional study of Genesis/GENEDIAB cohorts, the G-allele of rs17880135 was associated with incipient (OR 7.53, 95% CI 2.30–25.45, p=0.001), established (OR 6.04, 95% CI 1.52–23.91, p=0.01) and advanced nephropathy (OR 10.03, 95% CI 2.95–35.44, p=0.0003). SOD1 allelic variations were associated with the prevalence of diabetic nephropathy, with the incidence of microalbuminuria and with decreased eGFR in type 1 diabetic subjects. These results are consistent with an implication of oxidative stress in the pathophysiology of diabetic nephropathy and with the major role for antioxidant enzymes as a mechanism of renal protection.